Coppice restoration and conservation: a European perspective. Issue 3 (3rd May 2020) - Buckley, Peter
ABSTRACT: Coppice management has a long and ancient tradition in Europe, but still comprises over 14% of the forest area despite showing catastrophic declines in the past century. Contemporary trends in forestry towards continuous cover management have major implications for cosmopolitan and early-successional groups of species which rely on short rotations and regular disturbance, such as heliophilous plants and those with persistent seed, insectivore songbirds, butterflies, and many invertebrates requiring understorey flowering, pollen and nectar. Some species are considered of such high conservation value that they justify continued coppicing. When abandoned or converted to high forest, coppice vegetation shows increasing homogenisation and may lose some rare plant species, although shade-tolerant plants are largely unaffected. Accumulated litter and depositions of atmospheric nitrogen also threaten a future eutrophic response. At the same time, most aging coppices are too young to develop any significant old-growth and saproxylic features of conservation significance. Re-coppicing after 50–100 years of neglect has shown moderate success, with most early successional species recovering well and restoring species and functional biodiversity, assuming available sources in the surrounding landscape. Re-coppiced stools showed variable survival, but with usually sufficient regrowth to restore the former canopy, supplemented by natural regeneration. Some aspects of the coppice cycle can be delivered by alternative silvicultural methods, or manipulated in order to add missing old-growth characteristics. Ultimately a landscape which carries the full range of interconnecting growth stages, including coppice, will yield the greatest opportunities for biodiversity and conservation.